Anthropological Encounters of a Semiotic Kind - Parmentier, Richard (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2012)
This article prints for the first time two oral presentations occasioned by visits to Brandeis University by the medievalist Brigitte Miriam Bedos-Rezak and the classicist Gregory Nagy. The path-breaking and authoritative papers and books by these two scholars provide key insights for anthropologists working from a semiotic perspective. Bedos-Rezak’s proposal that the practice of sealing documents in pre-scholastic France can be seen as evidence for a general semiotic ideology of the “imprint” raises the possibility that the systematicity of sign processes and corresponding metasemiotic discourses reflects esoteric attempts to conceal pragmatic variability in favour of nostalgic coherence. Similarly, Nagy’s insistence on the importance of the performance contexts for the shaping of the Homeric epics is grounded in the recognition that the semiotic ideology of radical “decentring” found in these texts masks the changing course of their actual pragmatic enactment.